Ikere-Ekiti in Art and Cultural Narratives - dele jegede (Yoruba Studies Review, 2021)
Ikere, a city in Ekiti State of southwestern Nigeria, comes up often in the literature of art history on two principal accounts: first, its art and architecture, and second, its major annual fesitval. These are the two central concerns of this paper. In the first part, the unique architecture of the afin and the traditional sculptures that were its central feature present the opportunity to examine the interconnectedness of continuity and change, tradition and modernity, and the centrality of art in the Oba's quest for political pre-eminence. Ikere came to international attention through the vlrtuoslc sculptures of one of Africa's master carvers--Olowe (ca. 1873-1938), who lived in Ise-Ekiti, a town about 15 miles east of Ikere. In addition to offering new insights into the relevance of Olowe to Ikere, this essay posits a re-examination of the birth year of Olowe. In the second part, this essay dissects the Olosunta festival, which remains central to the collective identity of a people who subscribe to different religious doctrines. The early history of Ikere acknowledges the city as a site for the simultaneous reign of two rulers, the Ogoga and the Olukere. But it is the annual celebration of the Olosunta festival that serves as the rallying point for the indigenes of the city at the same time that it provides a time-honored structure for handling potentially explosive cultural and political contestations.